Manajemen SMK Negeri 1 Cimerak dalam Meningkatkan Disiplin Belajar - Dian Ardiansah; Dyah Ayuningtiyas; Neneng Nurmalasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to analyze management in improving learning discipline at SMK Negeri 1 Cimerak, with a focus on the strategies and approaches used by the school in achieving this goal. The research method used is a qualitative approach through in-depth interviews with management staff and direct observation in the school environment. The results of this research provide an in-depth understanding of how school management can influence student learning discipline. The main findings show that a holistic management approach, including the development of clear rules, personal coaching of students, and collaboration between school stakeholders, significantly improves student learning discipline.